Acupuncture vs. antispasmodics in the treatment of irritable bowel syndrome: An adjusted indirect treatment comparison meta-analysis - Shi, Yun-zhou; Tao, Qing-feng; Qin, Di; Chen, Min; Yu, Shu-guang; Zheng, Hui (Frontiers in Physiology, 2022)
Background: Acupuncture has been extensively applied to manage irritable bowel syndrome (IBS) in clinical practice in China. Some randomized controlled trials (RCTs) have demonstrated their efficacy, but it has rarely been compared with first-line antispasmodics to verify their effectiveness. Therefore, we compare acupuncture with antispasmodics in the treatment of IBS by using an adjusted indirect treatment comparison meta-analysis. Methods: Embase, OVID Medline, and the Cochrane Central Register of Controlled Trials databases were searched from inception to 14 March 2022, with no language restrictions. RCTs comparing antispasmodics or acupuncture with placebo or one of the antispasmodics were enrolled. The primary outcome of interest was the improvement of abdominal pain. And the secondary outcomes of interest were the relief of global IBS symptoms and adverse events. The random-effects model was utilized to pool data. The effect size was measured by standardized mean difference (SMD) or relative ratio, and the effectiveness of acupuncture and different antispasmodics were ranked by P-scores. Results: Thirty-five RCTs (n = 5,190) were included. The analysis showed that cimetropium, drotaverine, acupuncture, and pinarverium were superior over placebo in relieving abdominal pain; cimetropium (SMD, −3.00 [95%CI, −4.47 to −1.53], P-score = 0.99) ranked the most effective. In pairwise comparisons, acupuncture had a greater improvement than most antispasmodics except cimetropium and drotaverine in relieving abdominal pain, although the between-group difference was statistically insignificant. In the analysis of continuous outcome in the relief of global IBS symptoms, the result showed that pinaverium was more effective (SMD, 1.72 [95%CI, 0.53 to 2.92], P-score = 0.90) than placebo. Trimebutine and acupuncture had greater improvements than placebo, but no significant difference was shown between groups. In pairwise comparisons, acupuncture was more effective than pinaverium (SMD, −1.11 [95%CI, −1.94 to −0.28]) in relieving global IBS symptoms. In the analysis of adverse events, acupuncture had a lower adverse event rate than most of the other antispasmodics. Conclusion: Cimetropium, drotaverine, and acupuncture were all better than placebo in improving abdominal pain. Acupuncture was preferred over pinaverium in relieving global IBS symptoms, and acupuncture had lower adverse events than most antispasmodics.